2011
DOI: 10.1111/j.1464-410x.2010.10008.x
|View full text |Cite
|
Sign up to set email alerts
|

Semen quality after extracorporeal shockwave lithotripsy for the management of lower ureteric stones: a review of the literature

Abstract: language on semen analysis after lithotripsy. KEYWORDS extracorporeal shockwave lithotripsy, ESWL, distal ureteric calculi, semenWhat's known on the subject? and What does the study add? ESWL is effective in treating distal ureteric stones. However, the effect of lithotripsy on semen parameters and the testis has not been reviewed.This review reports that lithotripsy to distal ureteric stones causes a transient oligoasthenozoospermia for up to three months after lithotripsy. We have highlighted this important … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…This study reported the negative effect of high‐energy shock waves delivered by a lithotripter on human semen in vitro 28 . Since then, several clinical studies have evaluated the structure and testicular function of patients undergoing ESWL for distal ureteral stones (particularly close to the male reproductive organs), producing limited and contradictory evidence 26 . A recent meta‐analysis by Radfar et al.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This study reported the negative effect of high‐energy shock waves delivered by a lithotripter on human semen in vitro 28 . Since then, several clinical studies have evaluated the structure and testicular function of patients undergoing ESWL for distal ureteral stones (particularly close to the male reproductive organs), producing limited and contradictory evidence 26 . A recent meta‐analysis by Radfar et al.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] ESWT is generally described as a safe andrological procedure characterized by mild and transient side effects. 4,5,7 However, the still limited knowledge of the biological effects of shock waves, 2,3 the description of testicular damage following ESWL, 25,26 and espe-cially some recent pre-clinical studies showing the negative impact of low-intensity ESWT (Li-ESWT) on testicular function 8,27 have raised several concerns about the possible testicular effects of ESWT in ED or PD setting because of tissue contiguity between penis and testes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations